Marketing services and resources in information organizations - Yi, Zhixian (Chandos information professional series., 2018)
With the rapid development of information and communication technology and increasingly intense competition with other organizations, information organizations face a pressing need to market their unique services and resources and reach their user bases in the digital age. Marketing Services and Resources in Information Organizations explores a variety of important and useful topics in information organisations based on the authoru2019s marketing courses and his empirical studies on Australian academic librariansu2019 perceptions of marketing services and resources. This book provides an introduction to marketing, the marketing process, and marketing concepts, research, mix and branding, and much more. Readers will learn strategic marketing planning, implementation, and evaluation, effective techniques for promoting services and resources, and effective social media and Web 2.0 tools used to promote services and resources. Marketing Services and Resources in Information Organizations is survey-based, theoretical and practical. The advanced statistical techniques used in this book distinguish the findings from other survey research products in the marketing field, and will be useful to practitioners when they consider their own marketing strategies. This book provides administrators, practitioners, instructors, and students at all levels with effective marketing techniques, approaches, and strategies as it looks at marketing from multiple perspectives.